COVID-19 Clinical Outcomes in Solid Organ Transplant Recipients During the Omicron Surge. Issue 7 (11th April 2022) - Cochran, Willa; Shah, Pali; Barker, Lindsay; Langlee, Julie; Freed, Kristin; Boyer, Lauren; Scott Anderson, R.; Belden, Maura; Bannon, Jaclyn; Kates, Olivia S.; Permpalung, Nitipong; Mostafa, Heba; et al.
Abstract : Abstract :